Correction to: ACTN1 supports tumor growth by inhibiting Hippo signaling in hepatocellular carcinoma - Chen, Qian; Zhou, Xiao-Wei; Zhang, Ai-Jun; He, Kang (Journal of experimental & clinical cancer research, 2021)
ACTN1 supports tumor growth by inhibiting Hippo signaling in hepatocellular carcinoma [RAW_REF_TEXT] Qian Chen1 na1, [/RAW_REF_TEXT] [RAW_REF_TEXT] Xiao-Wei Zhou1 na1, [/RAW_REF_TEXT] [RAW_REF_TEXT] Ai-Jun Zhang 1 & [/RAW_REF_TEXT] [RAW_REF_TEXT] Kang He 2 [/RAW_REF_TEXT] Journal of Experimental & Clinical Cancer Research volume 40, Article number: 128 (2021) Cite this article [RAW_REF_TEXT] 62 Accesses [/RAW_REF_TEXT] [RAW_REF_TEXT] 1 Altmetric [/RAW_REF_TEXT] [RAW_REF_TEXT] Metrics details [/RAW_REF_TEXT] The Original Article was published on 07 January 2021 Correction to: J Exp Clin Cancer Res 40, 23 (2021) https://doi.org/10.1186/s13046-020-01821-6 Following publication of the original article [1], the authors identified minor errors in image-typesetting in Fig. 1; specifically in panels presented in Fig 1c, d, f and g. The corrected figure and caption are given below. Fig. 1 figure1 ACTN1 is highly expressed in HCC tissues and predicts a poor prognosis in HCC patients. a The mRNA expression level of ACTN1 in 20 paired HCC and NCL tissues was analyzed by real-time qPCR. b The protein expression level of ACTN1 in 5 paired HCC and NCL tissues. c Representative immunohistochemical images of ACTN1 in HCC, thrombus, NCL and normal liver tissues. ACTN1 supports tumor growth by inhibiting Hippo signaling in hepatocellular carcinoma [RAW_REF_TEXT] Qian Chen1 na1, Xiao-Wei Zhou1 na1, Ai-Jun Zhang 1 & Kang He 2 [/RAW_REF_TEXT] Journal of Experimental & Clinical Cancer Research volume 40, Article number: 128 (2021) Cite this article [RAW_REF_TEXT] 62 Accesses 1 Altmetric Metrics details